One novel HSD17B4 mutation in association with D-bifunctional protein deficiency: a case report and literature review - Xiong, Lu; Wang, Shiqing; Sun, Hui; Zhong, Tao; Li, Li; Zeng, Haijiang; Huang, Yubo (Frontiers in Pediatrics, 2026)
BackgroundD-Bifunctional protein, also called D-peroxisomal bifunctional enzyme which is encoded by HSD17B4 gene located in chromosome 5q21, catalyzes the second and third steps of preoxisomal β-oxidation of fatty acids and fatty acid derivatives. When HSD17B4 gene mutations cause varying degrees of decline in DBP function, it can lead to D-Bifunctional protein deficiency(D-BPD) which is a rare autosomal recessive discord. The typical symptoms include hypotonia and seizures.Case presentationA 4-day-old female infant was admitted due to recurrent seizures for 3 days. Main clinical manifestations included facial dysmorphism, poor responsiveness, hypotonia, feeding difficulties, refractory seizures, bilateral hearing impairment, and an electroencephalogram (EEG) showing focal sharp waves generalizing to widespread discharges. Whole-exome sequencing revealed a homozygous mutation in the HSD17B4gene originated from her parents: Exon6: c.344A>T (p.Asp115Val), a variant not previously reported. During her hospitalization, she received respiratory support, nasogastric feeding and antiepileptic treatment. One month after discharge, telephone follow-up revealed frequent recurrent seizures, the parents of the patient refused further treatment due to poor prognosis and financial constraints.ConclusionsThis article presents a case of a newborn who presented with hypotonia, feeding difficulties and refractory epilepsy shortly after birth, and was eventually diagnosed with D-bifunctional protein deficiency through whole-exome sequencing. The prognosis of this disease is poor, and symptomatic and supportive treatment is the main approach. Therefore, whole-exome sequencing is particularly important for definitive diagnosis when neonates present with generalized hypotonia, feeding difficulties and refractory epilepsy. In addition, a missense mutation [c.344A>T (p.Asp115Val)] is a newly discovered variant that deserve further study.